Pengaruh Pelatihan terhadap Kinerja Guru di Yayasan Amal Insan Rabbani - Satinah; Maman Suratman (Publikasi Indonesia, 2025)
Training plays an important role in improving teacher performance, especially in facing challenges in the dynamic world of education. Yayasan Amal Insan Rabbani organizes various trainings, including the 2013 Curriculum Implementation Training, English training, and the preparation of multimedia-based teaching materials. This study aims to analyze the influence of training on teacher performance in the foundation. The research uses descriptive and verification methods with a quantitative approach. Data were collected through questionnaires, interviews, and observations on the foundation's permanent teachers. The validity test using the Pearson product moment showed that all items were valid, while the data analysis was carried out with the F test and the t test to measure simultaneous and partial influences. The results showed that the training had a positive and significant influence on teacher performance, with a p-value < 0.001 in both tests. Respondents gave an average rating of 3.39 in the